(untitled) (Annals of Medical Research, 2021)
Aim: Status epilepticus (SE) is an important and distinct problem with its high morbidity and mortality. The need for early identification of SE to predict the course and prognosis of epilepsy have led us to investigate the clinical features associated with SE in patients with epilepsy in this study.Material and Methods: The information of the patients with epilepsy recorded comprised demographic features, type and etiology of seizures, age of onset of epilepsy, frequency of seizures, mono- or polytherapy treatment, history of convulsive SE, triggering factors for SE and brain magnetic resonance imaging findings. The data also included patients’ family history of epilepsy and history of febrile seizures, mental retardation.Results: A total of 610 patients with epilepsy (291 men, 319 women) were included in the study. It was found that 49 (8%) of the patients had at least one convulsive SE. Univariate logistic regression analysis showed that earlier onset of epilepsy, symptomatic/cryptogenic etiology, mental retardation, frequency of seizures ≥1/month, treatment with polytherapy, and abnormalities in neuroimaging are associated with SE (p=0.001, p0.001, p0.001, p0.001, p0.001 and p0.001, respectively). In multivariate logistic regression analysis; mental retardation (SE 0.380; 95% CI 0.186-0.825; p=0.014) and polytherapy (SE 0.392; 95% CI 0.158-0.735; p=0.006) were found to be independent factors related with SE. It was determined that 69% of patients had a triggering factor for SE and infection (65%) was the most common among these.Conclusion: The results of this study showed that there is a clear relationship between the occurrence of SE and mental retardation and treatment with polytherapy in patients with epilepsy. Symptomatic/cryptogenic etiology, early onset of epilepsy, high frequency of seizures and presence of abnormalities in neuroimaging are also associated with SE. Identification of these risk factors of SE will be helpful to initiate the appropriate treatment within a short time after diagnosis.